Implementasi Kebijakan Pemerintah Tentang Tenaga Bongkar Muat (TKBM) dan Peningkatan Kesejahteraan di Pelabuhan Yos Sudarso Ambon Provinsi Maluku - Kubangun, Arjuna Yusuf Maulana; Bahasoan, Aminah; Rolobessy, Mike J.; Selanno, Hendry (Jurnal Ilmiah Global Education, 2024)
The research was conducted to examine the implementation of government policy on charging frame energy (TCBM) as well as improving the well-being of staff at Yos Sudarso Ambon port. The results of the researchers' observations that the implementation of employee welfare standards has not been optimized in accordance with the regulations in force. Furthermore, wages paid to officials on the basis of boarding are not on the amount of income so it is still weak in the administration of financial administration. As for the research method used, it is qualitative descriptive by conducting in-depth interviews with the chosen informants. As for the findings of the research, (1). There's still recruitment of port workers based on the family system. Besides, there's still a weak motivation to do the hard work itself. (2). That the reality of a balanced and harmonious social life between the working groups in the port of Ambon can be used as an example of a good working relationship.